Accidental pharmacological poisonings in young children: population-based study in three settings. (3rd August 2018) - Bell, Jane C.; Bentley, Jason P.; Downie, Catriona; Cairns, Rose; Buckley, Nicholas A.; Katelaris, Annette; Pearson, Sallie-Anne; Nassar, Natasha
Abstract: Introduction: Pharmacological poisonings in young children are avoidable. Previous studies report calls to poisons centres, presentations to emergency departments (ED) or hospital admissions. There are limited data assessing concurrent management of poisonings across all three settings. We aimed to describe accidental pharmacological poisonings in young children across our Poisons Information Centre (PIC), EDs and hospitals. Methods: A population-based study in New South Wales, Australia, of PIC calls, ED presentations and hospital admissions for accidental pharmacological poisoning in children aged <5 years, 2007–2013. We examined trends, medicines responsible and subsequent management. Medicines were coded using ICD10-AM diagnosis codes (T36-50). Results: Over 2007–2013, pharmacological poisonings accounted for 67, 816 PIC calls, 7739 ED presentations and 2082 admissions. Rates (per 10, 000 children) of PIC calls declined from 220 to 178; ED presentations were stable (∼22–24), with a decrease in emergency cases offset by an increase in semi- or non-urgent presentations; hospital admissions declined (8–5). Most PIC calls related to "non-opioid analgesics" (25%), and "topical agents" (18%). Nearly every day, one child aged <5 years was admitted to hospital for poisoning. "Benzodiazepines", "other and unspecified antidepressants", "uncategorised antihypertensives", and "4-aminophenol derivatives" accounted for over one-third of all admissions. Most PIC calls (90%) were advised to stay home, 6% referred to hospital. One-quarter of ED presentations resulted in admission. Conclusions: Poisonings reported to PIC and hospitals declined, however, non-urgent ED presentations increased. Strategies to reduce therapeutic errors and access to medicines, and education campaigns to improve Poisons Centre call rates to prevent unnecessary ED presentations are needed.